PATTERNS OF DISABILITY IN VISUAL CULTURE - A. A. Rusanova; N. A. Lukyanova (Дискурс, 2017)
The concept of a pattern is considered as a generalized structure of a person's worldview which is formed under the influence of impressions produced by visual signs. The interpretation of the pattern as the basic concept of social relations is offered. Thus, it is often these patterns that are the stigma of disability that does not allow people with disabilities to integrate into modern society. The object of the research is to study corporality in mass culture. As the subject of the study, the authors identify patterns of a disabled body in modern visual culture. The aim of the research was to classify patterns of disability in modern visual culture using methodological approaches in the study (M. Merlot-Ponty, I. S. Kon, I. Bykhovskaya, N. A. Bugueva).